Thermodynamic Properties of InNa Liquid Alloy - Chakrabarti, SK; Jha, IS; Singh, BP (Scientific World, 2010)
The large asymmetry observed in the properties of mixing of indium-sodium liquid alloy is discussed on the basis of quasi-lattice chemical model. A special attention is given to the concentration dependence of free energy of mixing, entropy of mixing and heat of mixing. The results explain the observed asymmetry in the properties of mixing of InNa liquid alloys around equi-atomic composition. Key words: Complex forming alloys; Binary liquid alloys; Quasi-lattice model; Thermodynamic properties. DOI: 10.3126/sw.v6i6.2627 Scientific World, Vol. 6, No. 6, July 2008 16-18